2014
DOI: 10.1186/cc13981
|View full text |Cite
|
Sign up to set email alerts
|

Association between helicopter with physician versus ground emergency medical services and survival of adults with major trauma in Japan

Abstract: IntroductionHelicopter emergency medical services with a physician (HEMS) has been provided in Japan since 2001. However, HEMS and its possible effect on outcomes for severe trauma patients have still been debated as helicopter services require expensive and limited resources. Our aim was to analyze the association between the use of helicopters with a physician versus ground services and survival among adults with serious traumatic injuries.MethodsThis multicenter prospective observational study involved 24,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 15 publications
7
64
0
Order By: Relevance
“…E1 on GCS equals three-digit code on Japan Coma Scale (JCS) signifying that they were not arousable even with forceful stimulation. Because the JCS in the prehospital setting must be scored and recorded on the JTDB sheet, we used JCS to evaluate consciousness levels in the prehospital setting [9]. Assessment of consciousness levels based on the JCS are useful predictors of outcome in stroke patients [10].…”
Section: Methodsmentioning
confidence: 99%
“…E1 on GCS equals three-digit code on Japan Coma Scale (JCS) signifying that they were not arousable even with forceful stimulation. Because the JCS in the prehospital setting must be scored and recorded on the JTDB sheet, we used JCS to evaluate consciousness levels in the prehospital setting [9]. Assessment of consciousness levels based on the JCS are useful predictors of outcome in stroke patients [10].…”
Section: Methodsmentioning
confidence: 99%
“…The 17% represents the maximum effect of PS‐HEMS, which was significant, the 11% the minimum effect, which did not reach significance . The two remaining studies reporting in‐hospital mortality did not find a significant difference between the two groups …”
Section: Resultsmentioning
confidence: 93%
“…Overall, minor differences were found in patient characteristics between the PS‐HEMS and GEMS groups (Table ). One study reported a significantly higher age in the PS‐HEMS group, whereas two studies reported significantly lower age . Distance from scene to hospital was only reported in four studies of which two studies found a significantly longer distance in the PS‐HEMS group compared with GEMS (110 vs 77 km and 97 vs 63 km, both P < .01).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations